Time consistency, learning by doing and infant-industry protection: The linear case - Leahy, Dermot; Neary, J. Peter (Economic & Social Studies, 1994)
This paper examines the implications for strategic trade policy of diiferent assumptions about precommitment in a dynamic oligopoly game with learning by doing. Assuming that demands are linear, we find that the optimal first-period subsidy is increasing in the rate of learning with precommitment but decreasing in it if the government cannot precommit to future subsidies. The infant-industry argument is thus reversed in the absence of precommitment.
Keywords: Trade policy; Infant-industry; Learning